Memory Passing and Identity Formation: Generational Narratives in Vilkyškiai - Kulakauskienė, Dovilė (Respectus Philologicus, 2014)
Nations, confessions, and ideologies are continually mixing in frontier towns, creating a specific environment in which, on the one hand, an atmosphere of continual attrition and, on the other, tolerance and adaptation, has formed. The author has chosen to investigate the small town of Vilkyškiai, with its varied historical developments among different ethnic and confessional communities. The narratives of the young generation living in Vilkyškiai reflect the peculiarities of the local community’s identity formation. The youth not only learn the traditions of their own national or religious group and the main principles of moral values, but also constantly rethink the importance of their loved ones as well as their own value as people, ideas that are passed with memory narratives. Contemporary young people necessarily take into consideration contemporary cultural realia. The young generation of Vilkyškiai creates its own memory narratives and shapes new young people’s identities. While preserving their parents’ and grandparents’ historical experiences as images of the past, and at the same time taking on the local individual corporal identity, young people face a duality of identity. In this situation, the young generation of Vilkyškiai tends to give priority to the locally distinctive cultural identity of Lithuania Minor, calling themselves the inhabitants of this particular land. This permits them to feel distinct and interesting. Meanwhile, their parents’ and ancestors’ historical narratives are most often endorsed as the factor shaping their fundamental moral values.